2013
DOI: 10.1021/ol303567t
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Coupling of Polyfluorinated Arenes with Heteroarenes via C–F/C–H Activation

Abstract: The first palladium-catalyzed coupling of 2-pyridyl-polyfluoroarenes and benzoxazole, thiazole, benzothiazole, benzoimidazole, oxazole or oxadiazole via a concurrent C-F/C-H activation is described. Initial mechanistic studies showed that C-F activation of perfluoroarene is likely the rate-limiting step of the catalytic cycle. This protocol provides a useful and operationally simple process to functionalized polyfluoroarenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…235 The same authors reported an interesting coupling that involves a C-H activation of the non-fluorinated partner (Scheme 76, L = diphosphine). 236 In this case a 2-pyridinyl group as directing group was more effective than the oxazoline used before. The reaction can be extended to other polyfluorinated aryls taking into account that the same selectivity and reactivity limitations on the number of fluorine atoms mentioned for the Suzuki couplings apply.…”
Section: Scheme 74mentioning
confidence: 88%
See 1 more Smart Citation
“…235 The same authors reported an interesting coupling that involves a C-H activation of the non-fluorinated partner (Scheme 76, L = diphosphine). 236 In this case a 2-pyridinyl group as directing group was more effective than the oxazoline used before. The reaction can be extended to other polyfluorinated aryls taking into account that the same selectivity and reactivity limitations on the number of fluorine atoms mentioned for the Suzuki couplings apply.…”
Section: Scheme 74mentioning
confidence: 88%
“…236 The thermodynamics of the C-F activation by a metal complex may not be as unfavorable as one may think just looking at the C-F bond energy. Although this is quite a strong interaction the energy balance, that includes the formation of a M-F bond, may be more favorable for C-F cleavage than for other C-X activation processes (C-H for example).…”
Section: Oxidative Addition Of R-fmentioning
confidence: 99%
“…The pyridine directing group has been used in C-F/C-H cross-coupling as well as hydrodefluorination of fluoroaromatics with Et 3 SiH (Eqs. 76 and 77) [133,134]. Palladium has also been found to cross-couple perfluoroarenes to diaryl zinc compounds with the additive LiI (Eq.…”
Section: ð72; 73þ Catalytic Examplesmentioning
confidence: 99%
“…The preparation of these substances is typically performed by ac ondensation reactionb etween 2-aminophenols and either carboxylic acid derivatives [6] or aldehydes [7] or by the reaction of benzoxazoles with acyl chlorides [8] or aromatic aldehydes [9] that proceedst hrough ar ing-opening/ring-closing pathway.R ecently,t he direct CÀHb ond activation of benzoxazoles has emerged as potentially am ore efficient and convenient alternative for the straightforwards ynthesis of such compounds. Many elegant arylating reagents such as aryl halides, [10] arylsulfonyl derivatives, [11] aromatic carboxylic acid derivatives, [12] arylsilanes, [13] phenol derivatives, [14] boronic acids, [15] and others [10e, 16] have been reported. However,t he CÀHa rylation methods that employ these reagents generally suffer from the limited availability of substrates and harsh reaction conditions or requiret he use of expensive metal catalysts and ligand systems.…”
Section: Introductionmentioning
confidence: 99%